New species of lichens for Crimea peninsula from the pine forest (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The information about locations and ecologic peculiarities of nine new for Crimea peninsula species of lichens (Bryoria nadvornikiana (Gyeln.) Brodo & D. Hawksw., Buellia erubescens Arnold, Catillaria pulverea (Borrer) Lettau, Lecanora persimilis (Th.Fr.) Nyl., L. saligna (Schrad.) Zahlbr., Lepraria rigidula (B. de Lesd.) Tønsberg, Megalaria pulverea (Borrer) Haf. & Schreiner, Micarea misella (Nyl.) Hedl., Pertusaria pupllaris (Nyl.) Th. Fr.) are provided.
Keywords: pinea forest, lichens, Crimea peninsula.